If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 = 3(-1n + -8) + -2(1 + -8n) Reorder the terms: 52 = 3(-8 + -1n) + -2(1 + -8n) 52 = (-8 * 3 + -1n * 3) + -2(1 + -8n) 52 = (-24 + -3n) + -2(1 + -8n) 52 = -24 + -3n + (1 * -2 + -8n * -2) 52 = -24 + -3n + (-2 + 16n) Reorder the terms: 52 = -24 + -2 + -3n + 16n Combine like terms: -24 + -2 = -26 52 = -26 + -3n + 16n Combine like terms: -3n + 16n = 13n 52 = -26 + 13n Solving 52 = -26 + 13n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-13n' to each side of the equation. 52 + -13n = -26 + 13n + -13n Combine like terms: 13n + -13n = 0 52 + -13n = -26 + 0 52 + -13n = -26 Add '-52' to each side of the equation. 52 + -52 + -13n = -26 + -52 Combine like terms: 52 + -52 = 0 0 + -13n = -26 + -52 -13n = -26 + -52 Combine like terms: -26 + -52 = -78 -13n = -78 Divide each side by '-13'. n = 6 Simplifying n = 6
| 47-y=205 | | 3n+6/3=5 | | 66=-6(-5+x) | | x^2+70x-1050=0 | | 5(2x+1)=10 | | 13x-4=12x-1 | | P=2l+2wfore | | 26=6(5-4*.1666666667) | | 15x-9=10x+1 | | 6(x*x)-19x-7= | | 4.2q-5.7-5.3q=-0.1q-5.7 | | -13+n=-2 | | 3k-2(-5k-4)=2+3(5k-8) | | 12x+2=11x+5 | | 4(x*x)+9x+5= | | 12x=22+x | | 6x+4/2 | | t^2-t/2-10 | | 7-y/4=9 | | 9/9=72 | | x^2+70x-32100=0 | | 13yrd=inch | | 7p+8=6p+5 | | 2x^2-4x+7=1 | | x*x-6x-27= | | 1/3x/8=10 | | 5(-1)+2y=8 | | 26=6(30-24f) | | 13yrd= | | x*x-11x+24= | | 2a^3+10a^2= | | y*=77 |